0 valutazioniIl 0% ha trovato utile questo documento (0 voti)

8 visualizzazioni72 paginetransformasi linier

Dec 18, 2017

© © All Rights Reserved

PPT, PDF, TXT o leggi online da Scribd

transformasi linier

© All Rights Reserved

0 valutazioniIl 0% ha trovato utile questo documento (0 voti)

8 visualizzazioni72 paginetransformasi linier

© All Rights Reserved

Sei sulla pagina 1di 72

2. Matriks dan Operasinya

3. Determinan dan Sifat-sifatnya

UTS

4. Ruang Vektor

5. Basis dan Dimensi

6. Ruang Hasil Kali Dalam

7. Transformasi Linier

UTS

8. Matriks Transformasi Linier

9. Keserupaan

10. Nilai Eigen dan Vektor Eigen

11. Diagonalisasi

1

LINEAR TRANSFORMATIONS

Content

3

6.1 Linear Transformation

Definition

Let U and V be vector spaces. Let u and v be vectors

in U and let c be a scalar. A transformation T : U

V is said to be linear if

T(u + v) = T(u) + T(v)

T(c u) = c T(u)

U V

5

Example 1

Prove that the following transformation T: R2 R2 is linear.

T(x, y) = (x y, 3x)

Solution

Let (x1, y1) and (x2, y2) be vectors in R2.

T((x1, y1) + (x2, y2)) = T(x1 + x2, y1 + y2) (vector addition)

= (x1 + x2 y1 y2, 3x1 + 3x2) (definition of T)

= (x1 y1, 3x1) + (x2 y2, 3x2) (vector addition)

= T(x1, y1) + T(x2, y2) (definition of T)

Thus T preserves vector addition.

T(c(x1, y1)) = T(cx1, cy1) = (cx1 cy1, 3cx1) = c(x1 y1, 3x1)

= cT(x1, y1)

Thus T preserves scalar multiplication.

T is linear.

6

Example 2

Show that the following transformation T: R3 R2 is not linear.

T(x, y, z) = (xy, z)

Solution

Let (x1, y1, z1) and (x2, y2 , z2) be vectors in R3.

T((x1, y1, z1) + (x2, y2 , z2)) = T(x1 + x2, y1 + y2, z1 + z2)

= ((x1 + x2 )( y1 + y2), z1 + z2)

= (x1 y1 + x2 y2 + x1 y2 + x2 y1, z1 + z2)

and

T(x1, y1, z1) + T(x2, y2 , z2)) = (x1y1, z1) + (x2 y2 , z2)

= (x1 y1 + x2 y2, z1 + z2)

Thus, in general

T((x1, y1, z1) + (x2, y2 , z2)) T(x1, y1, z1) + T(x2, y2 , z2))

Since vector addition is not preserved, T is not linear.

7

Example 3

Show that the following transformation T: P2 P1 is linear.

T(ax2 + bx + c) = (a + b) x + c

Solution

Let ax2 + bx + c and px2 + qx + r be arbitrary elements of P2.

T((ax2 + bx + c) + (px2 + qx + r))

= T((a + p)x2 + (b + q)x + (c + r)) By vector addition

= (a + p + b + q) x + (c + r) By definition of T

= (a + b) x + c + (p + q) x + r

=T(ax2 + bx + c) + T(px2 + qx + r)) By definition of T

8

Example 3

Let k be a scalar.

T(k(ax2 + bx + c)) = T(kax2 + kbx + kc) By multiplication

= (ka + kb) x + kc By definition of T

= k((a + b) x + c)

=kT(ax2 + bx + c)

By definition of T

9

Example 4

interpreted as a mapping of Pn into itself.

D maps the element 4 x 3 3x 2 2 x 1 of P3 into 12 x 2 6 x 2 of P3 .

Let f and g be elements of Pn and c be a scalar. Then

D( f g ) Df Dg

D(cf ) cD( f )

The derivation thus preserves addition and scalar

multiplication of functions. It is a linear transformation.

10

Theorem 6.1.1

Let A be an m n matrix. Let x be a vector in Rn, interpreted as a

column matrix. The transformation T: Rn Rm, defined by T(x) = Ax, is

linear. Such a linear transformation is called a matrix transformation.

Proof

Let x and y be vectors in Rn, written as column matrices, and c be a

scalar.

T (x y ) A(x y )

Ax Ay

T ( x) T ( y ) Addition is preserved.

T (cx) A(cx)

cAx Scalar multiplication is

cT (x) preserved.

Thus the transformation is linear.

11

Example 5

Consider the linear transformation T defined by the following 3 2

matrix A. Find the image of an arbitrary vector under T, and use this

result to determine the image of the given vector x.

1 1

A 0 2 x 5

1

1 3

Solution

Since A is a 3 2 matrix, it defines a linear transformation T: R2R3.

We get 1 1 x y

T 0 2 2 y

x x

y 1 3 y x 3 y

Letting x = 5, y = 1 we get

6

5

T

2

2

1

12

Example 5

R2 R3

x x y

2y

y x 3 y

5 6

1 2

2

T

13

Composition of Transformations

U V W

14

Example 6

and T2(x, y) = (2x, y). Determine the image of (2, 3).

Solution

We get

15

Theorem 6.1.2

The composite of two linear transformation is itself a linear

transformation.

Proof

Let U, V and W be vector spaces and T1: U V, T2: V W be linear

transformations. Let u and v be vectors in U and c be a scalar. We use

the linearity of T1 and T2 to get

T2 (T1 (u)) T2 (T1 ( v)) T2 T1 (u) T2 T1 ( v)

T2 T1 (cu) T2 (T1 (cu)) T2 (cT1 (u)) cT2 (T1 (u)) cT2 T1 (u)

Thus T2 T1 is linear.

16

Non-commutative Composition

Scale then Translate: p' = T(S(p)) = (TS)(p)

(5,3)

Scale(2,2) (2,2) Translate(3,1)

(1,1) (3,1)

(0,0) (0,0)

(8,4)

Translate(3,1) (4,2) Scale(2,2)

(1,1) (6,2)

(3,1)

(0,0)

17

Example 7

Let T1(x) = A1x and T2(x) = A2x be defined by the following

matrices A1 and A2. Let T = T2 T1. Find the image of the vector

x under T. 1

A1 3 0 1 A2 1 2 x 4

4 2 0 4 0

2

Solution

A2 A1 1 2 3 0 1 5 4 1

4 0 4 2 0 12 0 4

Thus 1 23

T (x) 5 4 1 4

12 0 4 2 4

18

6.2 Matrix Transformation

Rotation about the Origin

20

Matrix Representation of Rotation

x ' r cos( )

r cos cos r sin sin

x cos y sin

y ' r sin( )

r sin cos r cos sin

y cos x sin

x' x cos sin x

Thus, ' T (a linear transformation)

y y sin c os y

Note tha t is positive for counterclockwise rotation,

negative for a clockwise rotation.

21

Matrix Representation

Let T: Rn Rm be a linear transformation. Consider the

standard basis S = {e1, e2, , en} for Rn as the set of column

matrices. Then for any vector v in Rn can be uniquely

written as

v = v1e1 + v2e2 + + vnen.

Since T is linear,

T(v) = T(v1 e1 + + vn en ) = v1 T(e1) + + vn T(en)

= [ T(e1) T(en) ] [v1 vn] t

The linear transformation T is then defined by the matrix

A = [ T(e1) T(en) ]

A is called the standard matrix of T.

22

Example 1

2x y

Determine the standard matrix of T

x

.

y 3 y

Solution

We find the effect of T on the standard basis.

1 2 0 1

T , T

0 0

1 3

These matrices are the columns of the standard matrix A.

A 2 1

0 3

Hence T can be written as a matrix transformation:

x

T 2 1

x

y 0 3 y

23

Dilation and Contraction

x x

Let T : R R be defined by T r , where r is a scalar.

2 2

y y

If r > 1, then T moves the points outward from the origin; it is called a

dilation of factor r. If 0 < r < 1, then T moves points inward toward the

origin; it is called a contraction of factor r.

Defined by

r 0

0 r

24

Reflection

x x

Let T : R R be defined by T that maps a point into its

2 2

y y

mirror image in the x axis. T is called a reflection.

1 0

Defined by

0 1

reflection in x axis

25

Example 2

Determine the matrix that describes a reflection in the x axis, following

by a rotation through /2, followed by a dilation of factor 3.

Find the image of the point 4

under this sequence of mappings. 1

Solution

The matrices that define the reflection, rotation, and dilation are,

respectively,

1 0 cos( / 2) sin( / 2) 3 0

, ,

0 1 sin( / 2 ) cos( / 2) 0 3

3 0 cos( / 2) sin( / 2) 1 0 3 0 0 1 1 0

0 3 sin( / 2) cos( / 2) 0 1 0 3 1 0 0 1

0 3

4 0 3 4 3 3 0

The image of the point is .

1 3 0 1 12

26

Transformations Defined by Invertible

Matrices

T(u) = Au

where A is a invertible matrix.

Theorem 6.3

An invertible linear transformation T maps

(a) lines into lines.

(b) segments of lines into segments of lines.

(c) parallel lines into parallel lines.

(d) lines through the origin into lines through the origin.

27

Example 3

Consider the transformation T: R2 R2 defined by

A 4 2.

2 3

Determine the image of the unit square under this transformation.

Solution

The unit square in R2 is the square whose vertices are,

respectively, the points

1 1 0 0

P , Q , R , O

0 1 1 0

Let us compute the images of these points under the

transformation. It is convenient to use the notation u Au to

discuss the images of specific points. Multiplying each point by

the matrix, we get P P Q Q R R O O

1 4 1 6 0 2 0 0

0 2 1 5 1 3 0 0

28

Example 3

Further, A (4 3) (2 2) 8 0. The matrix A is invertible, thus

line segments are mapped into line segments. We get

OP OP PQ PQ QR QR OR OR

The square PQRO is transformed into the parallelogram

PQRO.

29

Example 4

Let T be the orthogonal transformation defined by the following

orthogonal matrix A. Show that T preserve norms, and distances for the

vectors u and v. 1 1 2 3

A 1 1 , u , v

2 2

2 2 0 4

Solution

7

2 2

T (u) Au and T ( v) Av 1

2

2

u T (u) 2 and v T ( v) 5.

The angle between u and v is equal to the angle between T (u) and T ( v).

This angle is 53.13.

2 3 2

7

2

d , d , 1 17.

0 4 2 2

30

Translations

A translation is a transformation

T: Rn Rn defined by

T(u) = u + v

31

Example 4

translation

x x

T .

2

y y 1

Solution

The equation y = 2x + 3 describes points on the line of slope 2

and y intercept 3. T will slide this line into another line. We

want to find the equation of this image line. We get

x x 2 x 2 x 2 x

T

y y 1 2 x 3 1 2 x 4 y

We see that y = 2x for the image point. Thus the equation of

the image line is y = 2x.

32

6.3 Kernel and Range

Theorem 6.3.1

Let T: U V be a linear transformation. Let 0V and 0U be

the zero vectors of U and V. Then

T(0U) = 0V

That is, a linear transformation maps a zero vector into

zero vector.

Proof

Let u be a vector in U and let T(u) = v.

Let 0 be the zero scalar. Since 0u = 0U and 0v = 0V and T is

linear, we get

T(0U) = T(0u) = 0T(u) = 0v = 0V

34

Definition

Let T: U V be a linear transformation.

The set of vectors in U that are mapped into the zero

vector of V is called the kernel of T. The kernel is denoted

ker(T).

The set of vectors in V that are the images of vectors in U is

called image (range) of T. The image is denoted im(T).

35

Theorem 6.3.2

(a) The kernel of T is a subspace of U.

(b) The image of T is a subspace of V.

36

Example 1

Find the kernel and image of the linear operator

T(x, y, z) = (x, y, 0)

Solution

Kernel: ker(T) is the subset that is mapped into (0, 0, 0).

T(x, y, z) = (x, y, 0)

= (0, 0, 0), if x = 0, y = 0

Thus ker(T) is the set of all vectors of the form (0, 0, z). We write

this as

ker(T) = {(0, 0, z)}

Geometrically, ker(T) is the set of all vectors that lie on the z axis.

Image: The image of T is the set of all vectors of the form (x, y, 0).

im(T) = {(x, y, 0)}

Geometrically, im(T) is the set of all vectors that lie in the xy-

plane.

37

Example 1

38

Theorem 6.3.3

by the column vectors of A.

Proof

Let v be a vector in the image. There exist a vector u such

that T(u) = v. Express u in terms of the standard basis of Rn.

u = a1e1 + + anen

Thus

v = T(a1e1 + + anen) = a1T(e1) + + anT(en)

Therefore, the column vectors of A, namely, T(e1), , T(en),

span the image of A.

39

Example 2

Determine the kernel and the image of the transformation

defined by the following matrix.

1 2 3

A 0 1 1

Solution 1 1 4

A is a 3 3 matrix. Thus A defines a linear operator T: R3R3

with

T(x) = A(x).

Kernel:

1 2 3 x1 0 x1 2 x2 3 x3 0 x1 5r

0 1 1 x2 0 x2 x3 0 x2 r

1 1 4 x 0 x1 x2 4 x3 0 x3 r

3

The kernel is the set of vectors of the form (-5r, r, r).

ker(T) = {(-5r, r, r)}

Thus ker(T) is a one-dimensional subspace of R3 with basis (-5, 1, 1).

40

Example 2

Range: The image is spanned by the column vectors of A.

1 0 1 1 0 1 1 0 1 1 0 1

2 1 1 0 1 1 0 1 1 0 1 1

3 1 4 0 1 1 0 1 1 0 0 0

vector in the image will be a linear combination of these vectors.

s(1, 0, 1) + t(0, 1, 1)

Thus the image of T is

im(T) = {(s, t, s + t)}

Thus im(T) is a two-dimensional subspace of R3 with basis {(1,0,1),

(0,1,1)}.

41

Theorem 6.3.4

Let T: U V be a linear transformation. Then

dim ker(T) + dim im(T) = dim domain(T)

Example 3

Find the dimensions of the kernel and image of the linear

transformation T defined by the matrix

1 0 3

A 0 1 5

Solution 0 0 0

Observe that A is in row echelon form. The nonzero row vectors

are linearly independent. Thus rank(A) = 2, implying that

dim im(T) = 2.

The domain of T is R3; dim domain(T) = 3.

Therefore, dim ker(T) = 1.

42

One-to-one Transformation

in the image of T corresponds to just one element in the

domain of T. This means that T is one-to-one if T(u) = T(v)

implies that u = v.

43

Theorem 6.3.5

A linear transformation T is one-to-one if and only if the

kernel is the zero vector space.

Proof

(1) Assume that T is one-to-one. The kernel consists of all vectors

that are mapped into zero. Since T is one-to-one, the kernel

must consist of a single vector. However we know that the

zero vector must be in the kernel. Thus the kernel is the zero

vector space.

(2) Conversely, assume that the kernel is the zero vector space.

Let u and v be vectors such that T(u) = T(v).

T(u) T(v) = 0 T(u v) = 0

Thus u v is in the kernel. But the kernel only has the zero

vector. Therefore, u v = 0 or u = v. Thus T is one-to-one.

44

Theorem 6.3.6

The transformation T: RnRn, defined by T(x) = Ax, is one-

to-one if and only if A is invertible.

Proof

(1) Let T be one-to-one. Thus ker(T) = 0. The rank/nullity

theorem implies that dim im(T) = n. Thus the n columns of A

are linearly independent, implying that the rank(A) is n, and

|A| 0.

(2) Conversely, assume that A is invertible. This implies that the

rank of A is n and that its n column vectors are linearly

independent. This means that dim im(T) = n. The rank

(nullity) theorem now implies that ker(T) = 0. Thus T is one-

to-one.

45

Example 4

Determine whether the linear transformations TA and TB

defined by the following matrices are one-to-one.

1 2 5 7 2 0 1

A 0 1 9 8 B 3 4 2

0 0 1 3 0 7 5

Solution

(a) Since the rows of A are linearly independent, rank(A) = 3,

implying that dim im(TA) = 3. The domain of T is R4, so dim

domain(TA) = 4. By the rank/nullity theorem, dim ker(TA) =

1. Therefore, ker(TA) 0 and by Theorem 6.3.5, TA is not one-

to-one.

(b) It can be shown that |B| = 9 0. Matrix B is then invertible.

Thus, by Theorem 6.3.6, TB is one-to-one.

46

Theorem 6.3.7

Let T: U V be a one-to-one linear transformation. If

{u1, , un} is linearly independent in U, then {T(u1), ,

T(un)} is linearly independent in V.

Proof

Consider the equation

a1T(u1 ) + + anT(un ) = 0 (1)

for scalars a1, , an. Since T is linear, this is equivalent to

T(a1u1 + + anun ) = 0

T is one-to-one; thus the kernel is the zero vector space. Therefore,

a1u1 + + anun = 0

By linear independence of {u1, , un}, we have a1 = 0, , an = 0.

Returning to equation (1), this means that {T(u1), , T(un)} is

linearly independent.

47

6.4 Transformations and Systems

of Linear Equations

Relationships

49

Theorem 6.4.1

equations in n variables, Ax = 0, is a subspace of Rn.

Proof

Let T be the linear transformation of Rn into Rm defined by

A.

The set of solutions is the set of vectors in Rn that are

mapped by T into the zero vector.

The set of solutions is the kernel of the transformation and

is thus a subspace.

50

Example 1

Solve the following homogeneous system of linear equations.

Interpret the set of solutions as a subspace. Sketch the subspace

of solutions.

x1 2 x2 3 x3 0

x2 x3 0

Solution x1 x2 4 x3 0

Using Gauss-Jordan elimination we get

1 2 3 0 1 2 3 0 1 2 3 0 1 0 5 0

0 1 1 0 0 1 1 0 0 1 1 0 0 1 1 0

1 1 4 0 0 1 1 0 0 1 1 0 0 0 0 0

Thus x1 5r

x1 5x3 0 x1 5x3

x2 r

x2 x3 0 x2 x3

x2 r

51

Example 1

The solutions are vectors of the

form

( 5r, r, r)

These vectors form a one-

dimensional subspace of R3,

with basis ( 5, 1, 1). This

subspace is the kernel of the

transformation defined by the

matrix of coefficients of the

system

1 2 3

0 1 1 .

1 1 4

52

Theorem 6.4.2

Let Ax = y be a nonhomogeneous system of m linear

equations in n variables. Let x1 be a particular solution.

Every other solution can be written in the form x = z + x1,

where z is a vector in the kernel of the transformation T

defined by A.

53

Proof Theorem 6.4.2

solution. Thus Ax = y. Equating Ax1 and Ax, we get

Ax1 = Ax Ax Ax1 = 0 A(x x1) = 0 T(x x1) = 0

Thus x x1 is in the kernel of T; call it z. That is,

x x1 = z.

We can write

x = x1 + z

54

Example 2

Solve the following system of linear equations. Sketch the set of

solutions. x1 2x2 3x3 11

x2 x3 2

x1 x2 4x3 9

Solution

Using Gauss-Jordan elimination, we get

1 2 3 11 1 2 3 11 1 2 3 11 1 0 5 7

0 1 1 2 0 1 1 2 0 1 1 2 0 1 1 2

1 1 4 9 0 1 1 2 0 1 1 2 0 0 0 0

Thus x1 5r 7

x1 5x3 7 x1 5x3 7

x2 r 2

x2 x3 2 x2 x3 2

x2 r

The solutions are vectors of the form

55

Example 2

( 5r + 7, r + 2, r) = r(5, 1, 1) + (7, 2, 0)

arbitrary solution element of kernel a particular solution

to Ax = y to Ax = y

represented geometrically by

sliding the kernel, namely the

line defined by the vector ( 5,

1, 1), in the direction and

distance defined by the

vector (7, 2, 0).

56

Many Systems

y3, , all having the same matrix of coefficients A. Let T be

the linear transformation defined by A. Let x1, x2, x3, , be

particular solutions to these systems. Then the sets of

solutions to these systems are

ker(T) + x1, ker(T) + x2, ker(T) + x3

These sets are parallel sets, each being the ker(T)

translated by the amounts x1, x2, x3.

57

Example 3

Analyze the solutions to the following system of equations.

x1 2 x2 3 x3 x4 1

2 x1 3 x2 2 x3 x4 4

3 x1 5 x2 5 x3 5

x1 x2 x3 2 x4 3

Solution Solve using Gauss-Jordan elimination.

1 2 3 1 1 1 2 3 1 1 1 0 5 5 5

2 3 2 1 4 0 1 4 3 2 0 1 4 3 2

3 5 5 0 5 0 1 4 3 2 0 0 0 0 0

1 1 1 2 3 0 1 4 3 2 0 0 0 0 0

We get x1 5 x3 5 x4 5

x2 4 x3 3x4 2

Express the leading variables in terms of the free variables.

x1 5 x3 5 x4 5 x2 4 x3 3x4 2

58

Example 3

The arbitrary solution is

(5r 5s 5, 4r 3s 2, r , s)

Separate the parts of this vector as follows.

(5r 5s 5, 4r 3s 2, r , s )

Arbitrary solution to Ax = y

r (5, 4, 1, 0) s (5, 3, 0, 1) (5, 2, 0, 0)

kernel of mapping a particular solution

defined by A to Ax = y

with basis (5, 4, 1, 0), (5, 3, 0, 1). It is a plane through the origin.

The set of solutions to the given system is this plane translated

in a manner described by the vector (5, 2, 0, 0).

59

6.5 Matrix Representations of

Linear Transformations

Theorem 6.5.1

a basis for U. T is defined by its effect on the base vectors,

namely by T(u1), , T(un). The image of T is spanned by

{T(u1), , T(un)}.

on the whole domain.

61

Example 1

Consider the linear transformation T: R3 R2 defined as

following basis vectors of R3. Find T(1, -2, 3).

T(1, 0, 0) = (3, -1), T(0, 1, 0) = (2, 1), T(0, 0, 1) = (3, 0)

Solution

Since T is defined on basis vectors for R3, it is defined on the

whole space.

To find T(1, -2, 3), express the vector (1, -2, 3) as a linear

combination of the basis vectors and use the linearity of T.

T(1, -2, 3) = T(1(1, 0, 0) 2(0, 1, 0) + 3(0, 0, 1))

= 1T(1, 0, 0) 2T(0, 1, 0) + 3T(0, 0, 1))

= 1(3, -1) 2(2, 1) + 3(3, 0) = (8, 3)

62

Theorem 6.5.2

Let U and V be vector spaces with bases B = {u1, , un} and

B = {v1, , vm}, respectively, and T: U V a linear

transformation. If u is a vector in U with image T(u)

having coordinate matrices [u]B and [T(u)]B, then

T u B ' =Au B

where

A = T ( u 1 ) T ( u )

n B' T

B'

u T u

The matrix A thus defines a

transformation of coordinate vectors of U

in the same way as T transforms the u B T u B '

vectors of U. A is called the matrix A

representation of T (or matrix of T) with

respect to the bases B and B.

63

Example 2

Let T: U V be a linear transformation. T is defined relative to

bases B = {u1, u2, u3} and B = {v1, v2} of U and V as follows.

T(u1) = 2v1 v2

T(u2) = 3v1 + 2v2

T(u3) = v1 4v2

Find the matrix representation of T with respect to these bases

and use this matrix to determine the image of the vector

u = 3u1 + 2u2 u3.

Solution The coordinate matrices of T(u1), T(u2), and T(u3) are

2 3

, , and 1

-1 2 -4

These vectors make up the columns of the matrix of T.

2 3 1

A =

-1 2 -4

64

Example 2

Let us find the image of the vector u = 3u1 + 2u2 u3 using this matrix.

The coordinate matrix of u is

3

2 .

-1

3 11

We get 2 3 1

Au = 2 = .

B

-1 2 -4 -1 5

T(u) has coordinate vector 11 . Thus T(u) = 11v1 + 5v2.

5

65

Example 3

Let T: R3 R2 be the linear transformation defined by T(x, y, z) = (x

+ y, 2z). Find the matrix of T with respect to the bases {u1, u2, u3}

and {u1, u2} for R3 and R2, where

u1 = (1, 1, 0), u2 = (0, 1, 4), u3 = (1, 2, 3) and u1 = (1, 0), u2 = (0, 2)

Use this matrix to find the image of the vector u = (2, 3, 5).

T(u1) = T(1, 1, 0) = (2, 0) = 2(1, 0) + 0(0, 2) = 2u1 + 0u2

T(u2) =T(0, 1, 4) = (1, 8) = 1(1, 0) + 4(0, 2) = 1u1 + 4u2

T(u3) =T(1, 2, 3) = (3, 6) = 3(1, 0) + 3(0, 2) = 3u1 + 3u2

1

The coordinate vectors of T(u1), T(u2), and T(u3) are thus 2 , , and 3

0 4 3

2 1 3

A =

columns of the matrix of T: 0 4 3

66

Example 3

Let us now use A to find the images of the vectors u = (2, 3, 5).

We determine the coordinate vector of u. It can be shown that

u = (2, 3, 5) = 3(1, 1, 0) + (0, 1, 4) (1, 2, 3)

= 3u1 + 2u2 + ( 1)u3

3

The coordinate matrix of u is thus 2 .

The coordinate matrix

of T(u) is 3 1

2 1 3 5

2

0 4 3 5

1

Therefore, T(u) = 5u1 + 5u2 = 5(1, 0) + 5(0, 2) = (5, 10).

We can check this result directly using the definition T(x, y, z) = (x

+ y, 2z). For u = (2, 3, 5), this gives

T(u) = T(2, 3, 5) = (2 + 3, 2 5) = (5, 10)

67

Example 4

Consider the linear transformation T: P2 P1, defined by T(ax2 +

bx + c) = (a + b)x c. Find the matrix of T with respect to the basis

{u1, u2, u3} and {u1, u2} of P2 and P1, where

u1 = x2, u2 = x, u3 = 1 and u1 = x, u2 = 1

Use this matrix to find the image of u = 3x2 + 2x 1 .

Solution

Consider the effect of T on each basis vectors of P2.

T(u1) = T(x2) = x = 1x + 0(1) = 1u1 + 0u2

T(u2) = T(x) = x = 1x + 0(1) = 1u1 + 0u2

T(u3) = T(1) = 1 = 0x + (-1)(1) = 0u1 + (1)u2

The coordinate vectors of T(x2), T(x), and T(1) are thus 1 , 1 , and 0

0 0 -1

The matrix of T is thus

1 1 0

A =

0 0 -1

68

Example 4

3

2

-1

We get

3 5

1 1 0 2 =

0 0 -1

-1 1

69

Example 5

Let D d be the operation of taking the derivative. Find the

dx

matrix of D with respect to the basis {x2, x, 1} of P2.

D(x 2 ) 2x 0x 2 2x 1(1)

D(x ) 1 0x 2 0x 0(1)

D(1) 0 0x 2 0x 0(1)

The matrix of D is thus

0 0 0

A = 2 0 0

0 1 0

70

Theorem 6.5.3

Let U be a vector space with B and B. Let P be the transition

matrix from B to B. If T is a linear transformation on U,

having matrix A with respect to the first basis and A with

respect to the second basis, then

A = P1AP

Proof

Consider a vector u in U. Let its coordinate matrices

relative to B and B be a and a. The coordinate matrices of T(u)

are Aa and Aa. Since P is the transition matrix from B to B, we

know that a = Pa and Aa = P(Aa)

The second equation may be written P1Aa = Aa

Substituting a = Pa into the equation gives P1APa = Aa

The effect of the matrices P1AP and A as transformation on an

arbitrary coordinate vector a is the same. Thus these matrices

are equal.

71

Example 6

Consider the linear transformation T(x, y) = (2x, x + y) on R2. Find

the matrix of T with respect to the basis B = {(1, 0), (0, 1)} on R2.

Determine the matrix A with respect to B = {(-2, 3), (1, -1)}.

Solution The effect of T on the standard basis vectors is

T(1, 0) = (2, 1) = 2(1, 0) + 1(0, 1)

T(0, 1) = (0, 1) = 0(1, 0) + 1(0, 1)

2 0

The matrix of T relative to the standard basis is A =

1 1

Write the vectors of B in terms of those of B.

(-2, 3) = -2(1, 0) + 3(0, 1)

(1, -1) = 1(1, 0) 1(0, 1)

The transition matrix is

-2 1

P =

3 -1

Therefore

-1

-1 -2 1 2 0 -2 1 1 1 2 0 -2 1 = -3 2

A = P AP = =

3 -1 1 1 3 -1 3 2 1 1 3 -1 -10 6

72

## Molto più che documenti.

Scopri tutto ciò che Scribd ha da offrire, inclusi libri e audiolibri dei maggiori editori.

Annulla in qualsiasi momento.